Application Of Customer Relationship Management Through the Concept of Technology Adoption in the Broiler Jaya Broad Marketing Program - Nurfaizah, Ninda; Marsasi, Endy Gunanto (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
This research aims to study and analyze market conditions for broiler meat and factors that influence production, price, and demand for broiler chicken meat. After that, this research makes the right business design for the Jaya Broiler Chicken Business by optimizing the Broad Marketing Broiler Jaya program. This research was conducted at the Jaya Broiler Chicken Business house, Magelang, for six months. In completing the research, researchers used a qualitative approach and the data was obtained in three ways, observation, documentation in the form of photos and videos, and interviews. Innovation in digital marketing and processed products such as shredded chicken helps Broiler Jaya attract customers and increase sales turnover. Research recommends using technology such as Technology Adoption and Customer Relationship Management (CRM) in the Broad Marketing Broiler Jaya program to increase sales, implement digital marketing, and improve customer service.